Comparative Analysis Of Performance Levels Of Svm And Naïve Bayes Algorithm For Lifestyle Classification On Twitter Social Media - Fadlila Nurwanda; Winita Sulandari; Yuliana Susanti; Zakya Reyhana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Lifestyle is how individuals express themselves through their activities and interests and utilize their financial resources and available time. Twitter is a social network platform that allows people to express opinions and directly criticize various topics, including the recently widely discussed lifestyle topics. Topic classification on Twitter is central in facilitating the search, recommendation, and management of relevant content for users. This research aims to analyze public sentiment regarding lifestyle using 11,000 pieces of data with the keywords